Efficacy and Safety of Apixaban vs. Warfarin in Atrial Fibrillation Patients: Systematical Review and Meta-Analysis - Mokhamad Fahmi Rizki Syaban; Khadijah Cahya Yunita; Icha Farihah Deniyati Faratisha; Nabila Erina Erwan; Yoga Waranugraha; Adrian Rizal (Universitas Brawijaya, 2022)
Background: Various treatment strategies to treat AF and reduce its complications have been developed, including anticoagulant administration. Non-Vitamin K antagonist oral anticoagulants (NOAC) are recommended by current guidelines. Different anticoagulants revealed different safety and efficacy characteristic. The real-world evidence-based recommendation is still needed to improve AF management. This study aimed to disclose apixaban safety and efficacy profile compared with warfarin in a real-world population.Methods: We collected data from articles around the world studies comparing Apixaban and Warfarin in NVAF patients recorded online from studies published around 2015 to 2020 that we were taking from a scientific database such as Embase ProQuest, PubMed, and Cochrane based on inclusion criteria. Data analysis was carried out using Review Manager Version 5.4.1 (Cochrane, Copenhagen, Denmark) using Mantel-Haenzel statistical method for categorical data to measure Relative Risk (RR) and 95% Confident Interval (CI). We use a random-effect analysis model if P for heterogeneity (pHet <0.1) and a fixed-effect analysis model if pHet ≥0.1.Results: Apixaban show a benefit in preventing ischemic stroke (RR = 0.51; 95% CI=0.40-0.66; p = <0.00001) ischemic stroke/systemic embolism (RR = 0.63; 95% CI=0.50-0.81; p = <0.0002), and all-cause mortality (RR = 0.54; 95% CI=0.40-0.74; p = <0.0001) relative to Warfarin. Apixaban also show benefit to prevent major bleeding (RR = 0.49; 95% CI=0.41-0.58; p = <0.0001), GI bleeding (RR = 0.46; 95% CI=0.36-0.60; p = <0.0001), and intracranial hemorrhage (RR = 0.45; 95% CI=0.36-0.57; p = <0.0001) relative to Warfarin.Conclusions: Apixaban is over warfarin in efficacy and safety. Apixaban has a safer profile in reducing the risk of major bleeding, GI bleeding, and intracranial hemorrhage in AF patients.